Kaplan Meier's Analysis of Clinical Improvement Of Defecation Frequency In Pediatrics Patient With Diarrhea That Given Vitamin D As Adjuvant Therapy - Nurcholid Umam Kurniawan; Sutrimo Usali R; Endang Darmawan (Universitas Ahmad Dahlan, 2021)
Diarrhea is the second leading cause of death in children under 5 years after pneumonia with a mortality prevalence of 8%. Diarrhea is a digestive disease with signs of bowel movements with a sudden consistency of loose stools 3 times or more in 24 hours, mostly caused by microorganisms (bacteria and viruses). The cure rate for diarrhea after receiving fluid replacement therapy and antibiotics for diarrhea caused by bacteria is quite high, but the mortality rate due to diarrhea is still high, therefore there needs to be an effort to add therapy to improve patient clinical outcomes. Vitamin D is known to play a role in the body's defense function, both in natural and adaptive immunity and plays a role in the body's defense in cases of infections, allergies, and autoimmunity. This study is an experimental double blind randomized clinical trial which was analyzed using Kaplan Meier. The research subjects were children aged 6 months to 18 years who were divided into two groups, namely the treatment group (n = 35) and the control group (n = 35). The treatment group received vitamin D and for the control group received a placebo. The data taken includes the results of the frequency of defecation of patients. The results of this study indicate that vitamin D is effective in accelerating the reduction in the frequency of defecation in children with diarrhea. Â Keywords: Diarrhea, Vitamin D, Defecation, Kaplan Meier